A reading of Vonnegut's major novels as works of metafiction - Babaei, Abdulrazagh (2013)
A reading of Vonnegut‘s major novels as metafiction grows out of the diverse critical reactions to the paradoxical nature of Kurt Vonnegut's works as part of contemporary American literature. For Vonnegut, the fact that the autonomy of literature is a basic tenet of postmodernism does not make the challenge of pragmatic experimental literature any less real. Rather, Vonnegut suggests a kind of fiction that aims to alter the world and its inhabitants‘ deeds while providing the basic prerequisites of postmodern fiction. Such innovative juxtaposition takes place through fictional writing, called metafiction, that self-consciously and systematically draws attention to its status as an artefact in order to pose questions about the relationship between fiction and reality. Metafiction helps Vonnegut to propose fiction that connects literature and the real world, thus providing his idealistic aspiration for artists as agents of change. Exposing the construction of a fictional cosmos and the laying bare of that cosmos, metafictional strategies of authorship, frame-breaking, play, intertextuality and parody as the literary means of self-reflexive fiction display the uncertain, insecure, self-questioning and culturally pluralistic aspects of world narratives. Religion, history and American culture are the ―grand narratives‖ to which Vonnegut offers his readers a better understanding of their fundamental structures by providing analogous counterparts in self-conscious narratives. By examining three selected novels, Cat’s Cradle,Slaughterhouse-Five and Breakfast of Champions, as examples of metafiction, the study shows how Vonnegut unmasks the grand narratives of American culture while offering ingenious and entertaining stories that call for readers with ―imagination and ordering faculties alert and at work‖. Vonnegut, in his metafictional trilogy while developing a blueprint for his art, adamantly exploits metafiction to give an accurate model for understanding the contemporary experience of the world as a series of constructed provisional systems rather than eternal verities.